Association between alendronate, serum alkaline phosphatase level, and heterotopic ossification in individuals with spinal cord injury. (March 2015) - Ploumis, Avraam; Donovan, Jayne M.; Olurinde, Mobolaji O.; Clark, Dana M.; Wu, Jason C.; Sohn, Douglas J.; O'Connor, Kevin C.
Abstract : Context/objective: Only sparse evidence exists regarding the effectiveness of oral alendronate (ALN) in the prevention of heterotopic ossification (HO) in patients with spinal cord injury (SCI). The objective of this study is to investigate the protective effect of oral ALN intake on the appearance of HO in patients with SCI. Study design: Retrospective database review. Setting: A Spinal Cord Unit at a Rehabilitation Hospital. Participants: Two hundred and ninety-nine patients with SCI during acute inpatient rehabilitation. Interventions: Administration of oral ALN. Outcome measures: The incidence of HO during rehabilitation was compared between patients with SCI receiving oral ALN ( n  = 125) and patients with SCI not receiving oral ALN ( n  = 174). The association between HO and/or ALN intake with HO risk factors and biochemical markers of bone metabolism were also explored. Results: HO developed in 19 male patients (6.35%), however there was no significant difference in the incidence of HO in patients receiving oral ALN or not. The mean odds ratio of not developing versus developing HO given ALN exposure was 0.8. Significant correlation was found between abnormal serum alkaline phosphatase (ALP) levels and HO appearance (P < 0.001) as well as normal serum ALP and ALN intake (P < 0.05). Conclusion: Even though there was no direct prevention of HO in patients with SCI by oral ALN intake, abnormal serum ALP was found more frequently in patients with HO development and without oral ALN intake. This evidence could suggest that ALN may play a role in preventing HO, especially in patients with acute SCI with increasing levels of serum ALP.